A Study On Determinants Of Sexual Harassment Among Female Employees And It’S Effect On Turnover Intention & Work Engagement - Idris, Jismanisa (2014)
Sexual harassment is a misconduct behaviour that affects the wellbeing and productivity on an organization and it was an extremely detrimental, time consuming and a mojor cause of workplace tension and job dissatisfaction. Thus, this study intends to give an overview on what is the sexual harassment and to identify the determinants Organization Climate (Organization’s Responsibility, Organization’s Policy and Training), Leadership Skill, Personalities (Neurotism, Agreeableness, Openness, Conscientiouness and Exteroversion) and Job Insecurity of Sexual Harassment among female employees and the effect of Sexual Harassment on Turnover Intention and Work Engagement. Data were collected from 151 female employees in various workplace and profession in Penang with outcomes, this study designed to examine the Organization Climate (Organization’s Responsibility, Organization’s Policy and Training), Leadership Style, Personalities (Neurotism, Agreeableness, Openness, Consciencetioness and Extroversion) and Job Insecurity as a physical outcomes of sexual harassment among female employees in the workplace. Further to that, this study also designed to examine the links of Sexual Harassment toward Turnover Intention and Work Engagement. In addition, the finding reveal that there are positively related but note significate for Organization’s Responsibility, Organization’s Policy and Agreeableness to Sexual Harassment which shows that the commitment and support of the organization to stop sexual harassment in organization. Findings also revealed that the sexual harassment has significantly related to Turnover Intention and also Work Engagement. xiii twelve hypotheses were formulated in order to achieve the objective of the study. As an